A second-order accurate non-intrusive staggered scheme for the interaction of ultra-lightweight rigid bodies with fluid flow. (1st December 2020) - Kadapa, Chennakesava
Abstract: This paper presents a staggered scheme with second-order temporal accuracy for fluid–structure interaction problems involving ultra-lightweight rigid bodies. The staggered scheme is based on the Dirichlet–Neumann coupling and is non-intrusive. First, the spectral properties of the staggered scheme are studied and also compared against the monolithic scheme using a linear model problem. Later, the suitability and effectiveness of the staggered scheme for problems involving incompressible flows and lightweight rigid solids are illustrated by using the examples of galloping of a square cylinder and lock-in of a circular cylinder for mass-ratio values as low as 0.01. This is the first time in the literature flow-induced vibrations of rigid bodies with such low mass ratio values are successfully simulated using a staggered scheme. Two different fluid solvers are considered to illustrate the non-intrusive nature of the proposed scheme. Guidelines for choosing the relaxation parameter are also provided. With its iteration-free nature and with a single (relaxation) parameter, the proposed staggered scheme renders itself as an accurate and computationally efficient scheme for fluid–rigid body interaction problems, including those involving lightweight structures. Highlights: A second-order accurate staggered scheme for fluid–rigid body interaction. Accuracy and stability characteristics are presented using a linear model problem. The non-intrusive nature of the staggered-scheme is illustrated using two different CFD solvers. Successful simulation of vortex-induced vibrations of circular cylinder and square bodies for mass ratio values as low as 0.01.